Komunikasi Keluarga Dalam Memotivasi Mahasiswa Rantau Asal Papua Menempuh Pendidikan Tinggi di Jakarta - Wowor, Hana Aviela Fedria; Sary, Marisa Puspita; Putri, Maulina Larasati (PERSPEKTIF, 2024)
This article aims to determine the role of family communication in motivating higher education. Public education in Papua is not yet evenly distributed as a whole due to constraints on facilities, means, or understanding the importance of education itself. This research was conducted by conducting in-depth interviews with overseas students from Papua who were continuing their higher education (or studying) in Jakarta. Based on the Symbolic Interaction theory, an action will do something because there is an understanding of the meaning. This research shows that the five students interviewed have the same sense of the meaning of education, that education is important for a better future. So they consider college (thing) as something that must be done to achieve a good future. Therefore, they chose to study in Jakarta as a form of action (act). In the end, the meaning of the importance of education and what motivates them to study in Jakarta is the family, especially parents. Parents, as the smallest institution, who have been together since childhood, have been involved in providing education and giving them views on good education and the goals of education.